Health Status of Elderly in India-The Path Ahead - Mathur, Shradha; Mathur, Navin (Indian Journal of Community Health, 2015)
Health of the ageing individuals has become a rising concern, particularly due to unpreparedness, unresponsiveness and lack of negligence to this specific population group and ignored status of geriatrics in India. The objectives of the present study are (1) To explore the demographic structure of the Indian elderly population, (2) To reflect on the factors responsible for health problems and deaths among the Indian elderly, and (3) To critically evaluate the situation of health expenditure in India. The article is based on analysis of secondary data from World Health Organization (W.H.O), Ministry of Statistics and Programme Implementation, and Ministry of Home Affairs, the Government of India. The data has been analyzed and presented thematically in order of the objectives listed. The authors propose pragmatic, operational and contextually significant key recommendations for the improvement and enhancement of health status of elderly persons in India